Modelling and simulation of DC chopper using MATLAB/Simulink : article / Maruan Ibrahim - Ibrahim, Maruan (2010)
A 4 Quadrant DC-to-DC converter is used to control the DC motor drive that require forward and reverse motoring as well as forward and reverse braking. DC motor drive system controlled by Pulse Width Modulation (PWM) technique are expected to replace the conventional phase controlled system. This is due to their simple control, high reabiality,Iow cost and fast response. This paper present work on development of four quadrant DC-to-DC converter using the Power system Block Set (PSB) within the MATLAB/Simulink (MLS) enviroment. The output is being synthesized using Pulse Width Modulation('EWM) technique. The FQDC is supplied by a **V DC voltage source; the load takes the form of a pure resistive, inductance with battery E representing a back emf of a de motor.